Correlation between nasal anatomical characteristics in newborns and short binasal prong dimensions - Débora F.C. Ribeiro; Adriane M. Nakato; Paula K. Hembecker; Beatriz L. Fernandes; Percy Nohama (Jornal de Pediatria, 2024)
Objective: To correlate the nasal anatomical characteristics of newborns with the dimensions of short binasal prongs. Method: Observational, cross-sectional study carried out in two hospitals in southern Brazil. The authors evaluated 1620 newborns with neonatal data and nasal dimensions. To measure the dimensions of the nasal region, the authors considered the width of the medial columella, the right nostril diameter, and the left nostril diameter. These data were correlated with the dimensions of two models of short binasal prongs. Results: Of the total newborns evaluated, 807 were female (49.8%), and 813 were male (50.2%). The majority were white (96.2%). The mean gestational age was 37.4 ± 2.9 weeks, ranging from 22 to 42 weeks. The birth weight was 2946.8 ± 699.3 g, ranging from 490.0 to 4740.0 g. Most of the nasal measures were significantly larger than both prong model measurements. Conclusion: The sizes of short binasal prongs available on the Brazilian market do not match the nasal anatomical characteristics of newborns.